Yardangs in terrestrial ignimbrites: synergistic remote and field observations on Earth with applications to Mars - de Silva, S. L. (2010)
The conditions of formation and the form of yardangs in ignimbrites in the Central Andes of Chile, Bolivia, and Argentina may be the most convincing terrestrial analog to the processes and lithology that produce the extensive yardangs of the Medusae Fossae Formation (MFF) of Mars. Through remote and field study of yardang morphologies in the Central Andes we highlight the role that variable material properties of the host lithology plays in their final form. Here, ignimbrites typically show two main facies: an indurated and jointed facies, and a weakly to poorly indurated, ash- and pumice-rich facies. Both facies are vertically arranged in large (erupted volume >100's of km3) ignimbrites resulting in a resistant capping layer, while smaller (10's of km3) ignimbrites are made predominantly of the weakly indurated facies. The two facies have quite different mechanical properties; the indurated facies behaves as strong rock, fails by block collapse and supports steep/vertical cliffs, while the non-indurated facies is more easily eroded and forms gentle slopes and manifests as more subdued erosional forms. In response to aeolian action, the presence of an upper indurated facies results in large, elongate, high aspect ratio (1:20–1:40) megayardangs that form tall (100 m), thin ridges with steep to vertical walls. These are built on a broad apron of the weakly indurated facies with abundant fallen blocks from the upper indurated facies. These terrestrial megayardangs appear to be analogous to megayardangs with associated block fields seen on Mars. Smaller-volume, weakly indurated ignimbrites are sculpted into smaller, stubbier forms with aspect ratios of 1:5–1:10 and heights rarely exceeding 10 m. Excavation of a windward basal moat suggests an erosional progression like that seen in incipient yardangs on Mars. Excavation rates of 0.007–0.003 cm/year are calculated for the weakly indurated ignimbrites. While a persistent strong unidirectional wind is the dominant parameter controlling yardang formation and orientation, a role for flow separation and vorticity is also suggested by our observations at both yardang types. While the indurated facies is commonly pervasively jointed, jointing is of secondary importance in controlling yardang orientation. Serrated margins, a common feature on Mars, result from oblique intersections of jointing with yardang flanks or scarps of ignimbrite. The processes of yardang formation we describe from ignimbrites from the Central Andes are not necessarily specific to ignimbrites, but do connote that degree and distribution of induration is a major control in yardang formation and this has implications for the lithology of the MFF on Mars.